2020
DOI: 10.1021/acsomega.0c04830
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Toxicity of Polystyrene Nanoplastics inCaenorhabditis elegansand the Regulating Effect of Presenilin

Abstract: As one of the most widely used materials, plastic polymer fragments can abrasively degrade into microplastic (MP) and smaller nanoplastic (NP) particles. The present study aimed to investigate the influence of particle size on neurodevelopmental toxicity induced by polystyrene nanoplastics (PS-NPs) in Caenorhabditis elegans and to explore the underlying potential mechanism. C. elegans were exposed to different concentrations of PS-NPs with various sizes (25, 50, and 100 nm) for 72 h. Our results showed that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 54 publications
6
17
0
4
Order By: Relevance
“…4 ), albeit it was beyond the capabilities of our study to confirm the increased secretion or activity of SOD3 enzyme in the extracellular milieu. This finding is also supported by previous studies that found oxidative stress induced by microplastic-mediated interference in mitochondrial function, suppression of cellular antioxidant systems, and increased generation of reactive oxygen species (Abidli et al 2021 ; An et al 2021 ; Chen et al 2021 ; Cortés et al 2020 ; Liu et al 2020 ; Wei et al 2021 ).
Fig.
…”
Section: Discussionsupporting
confidence: 86%
“…4 ), albeit it was beyond the capabilities of our study to confirm the increased secretion or activity of SOD3 enzyme in the extracellular milieu. This finding is also supported by previous studies that found oxidative stress induced by microplastic-mediated interference in mitochondrial function, suppression of cellular antioxidant systems, and increased generation of reactive oxygen species (Abidli et al 2021 ; An et al 2021 ; Chen et al 2021 ; Cortés et al 2020 ; Liu et al 2020 ; Wei et al 2021 ).
Fig.
…”
Section: Discussionsupporting
confidence: 86%
“…MNPs can induce neurodevelopmental toxicity depending on particle size, which is mediated by mitochondrial damage and dopamine reduction. Data from the mutant test demonstrated that improved expression of sel-12 and hop-1 is involved in the regulation of MNP-induced oxidative stress, mitochondrial damage, and neurodevelopmental toxicity in Caenorhabditis elegans [ 74 ].…”
Section: Toxicities Of Micro- and Nanoplastics On Mitochondriamentioning
confidence: 99%
“…In C. elegans the expression of the dopaminergic neuron reporter dat-1pr::GFP shows decreased fluorescence upon exposure to polystyrene nanoplastics (PS-NP). This was also associated with decreased mitochondria function and increased oxidative stress ( Liu et al, 2020c ), suggesting dopaminergic specific toxicity upon PS-MP exposure. The exposure to UV-aged PS-MPs caused more severe dopaminergic defects than virgin MPs, probably due to the leaching of toxic materials ( Chen et al, 2021a ).…”
Section: The Effects Of Microplastics and Nanoplastics On Reproductiv...mentioning
confidence: 99%